Human resource Role in Change management During cross border Mergers - Yousaf Iqbal,, Dr. Fareeha Zafar (Journal of Medical Biomedical and Applied Sciences, 2014)
Human resource in todayâs age and time has a strategic role to be played in change processes. The following paper analyzes the key factors that can lead for a successful merger and how HR can assist in this change. The 2Câs namely culture and communication holds the key for success and failure depending upon the implied strategy by the top management and its application by the HR department. Moreover, change management and mergers have been analyzed with case studies from cross border mergers.